Excelência em gestão na construção civil: um estudo exploratório - Garcia, Marcelo Moraes (2010)
The context in which large Brazilian construction companies are incorporated in the year 2010, with increased real estate financing and government investment, has provided great opportunities in this sector. This study aims to evaluate a group of 10 large builders, focusing on residential or commercial work, according to the criteria of the Management Excellence Model (MEM) of the National Quality Foundation (NQF). A questionnaire was adapted from NFQ and answered by the president or CEO of companies surveyed, as the sole builder of winning the National Quality Award (NQA). The survey results showed that the companies surveyed have a good level of quality management, with companies focusing on business performance works more subtly. Data analysis was performed considering the seven criteria: customers, society, leadership, strategies and plans, people, processes, and finally information and knowledge. The main conclusion of this study is that despite the good level of management of the companies surveyed, there is an imbalance of the shares in these companies as to the criteria of MEM, with overvaluation of the criteria procedures, and reduced recovery of actions directed to the criteria society. In comparison with the company winning the NQA, one of the companies showed indicators of high excellence in its management process and may initiate a process of competition to the NQA